Spironolactone in pulmonary arterial hypertension: results of a cross‐over study. (1st April 2020) - Safdar, Zeenat; Frost, Adaani; Basant, Arya; Deswal, Anita; O'Brian Smith, E.; Entman, Mark
Abstract : The renin–angiotensin–aldosterone system is implicated in the pathophysiology of pulmonary arterial hypertension. We undertook this study to determine the effects of spironolactone, a mineralocorticoid receptor blocker, on collagen metabolism in pulmonary arterial hypertension patients. After obtaining institutional review board approval and informed consent, 42 pulmonary arterial hypertension patients were prospectively enrolled and 35 patients completed the 16‐week randomized double‐blinded crossover clinical trial. Subjects received 50 mg spironolactone or placebo and at the end of week 8, treatment arm was switched. Circulating levels of collagen biomarkers, brain natriuretic peptide, and aldosterone levels were measured, and six‐minute walk distance, liver function tests, and echocardiogram data were collected at weeks 0, 8, and 16. Mean age was 45 ± 15 years and 87% were females. At baseline, brain natriuretic peptide and aldosterone levels were 74 ± 95 pg/ml and 7 ± 8 pg/ml, respectively. There was no change in the levels of amino‐terminal propeptide of procollagen type III (PIIINP), MMP‐9, TIMP‐1, and MMP‐9/TIMP‐1 ratio at weeks 8 and 16 compared to baseline values in placebo arm and treatment arm. The baseline six‐min walk distance was 436 ± 115 meters at baseline and no change in walk distance was noted at weeks 8 and 16 ( P  = 0.372). None of the patients developed hyperkalemia or liver function test abnormalities at weeks 8 and 16 requiring discontinuation of study drug. Our study showed no change in collagen metabolite levels in pulmonary arterial hypertension patients treated with spironolactone. Spironolactone was safe and well tolerated by pulmonary arterial hypertension patients with no increased hyperkalemia or liver function test abnormalities.